Effectiveness of the Vital Aging program to promote active aging in Mexican older adults - Mendoza-Ruvalcaba, Neyda Ma (Clin Interv Aging, 2016)
INTRODUCTION: Aging is not only a population phenomenon but also an experience and an individual reality. Vital Aging(®) is a program that considers active aging as the lifelong adaptation process of maximizing health and independence, physical and cognitive functioning, positive affect regulation and control, and social engagement. Through its different versions and editions, it has demonstrated being an effective program to promote active aging. The aim of this study is to determine the effectiveness of the “face-to-face” and “combined” versions of the program to promote active aging in Mexican older adults trial. METHODS: Seventy-six older adults aged 60 years and over participated in a quasi-experimental study and were recruited in a senior center to participate in the two experimental conditions: Vital Aging face-to-face (VA-FF) (n=35) and Vital Aging combined (VA-C; multimedia/face-to-face) (n=15), and the remaining 26 adults were assigned to a control group. Pretest and posttest assessments were performed after the theoretical–practical intervention. Mean differences and size effects were calculated for estimating the effect of the program. RESULTS: At the end of the study, participants showed improvements in the active aging outcome measures. Positive effects were observed in the frequency of intellectual, cultural – artistic, and social activities, perceptions of aging, satisfaction with social relationships, and self-efficacy for aging. Additionally, those who participated in VA-FF showed better memory performance, meta-memory, and a trend to report less memory problems, while older persons in VA-C showed a trend to have better life satisfaction. No effects were observed in physical activity, frequency of social relationships, and subjective health. CONCLUSION: Findings show that the Vital Aging program in face-to-face and combined versions encourages active aging in Mexican older persons. These results are in general similar to those found in editions performed in Spain, revealing its consistency as a cross-cultural practical initiative for promoting active aging.